2006
DOI: 10.1002/j.1839-4655.2006.tb00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Privatising health: the demise of MEDICARE?

Abstract: Health policy was an integral component of the postwar welfare state, which represented a nationally based class compromise providing concessions in the form of income support and service provision outside the ambit of the market. In Australia, development of a universal health system was delayed until the introduction of Medibank, and subsequently Medicare. Since its inception, Medicare has been subjected to retrenchment pressures that have dominated welfare state developments since the mid 1970s. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In provision, there is also a difference between right and left. Although Howard’s Conservative federal government had supported private sector utilization and has promoted the privatization of “problem” public hospitals (Cook, 2006), the ALP has opposed privatization of public hospitals (ALP, 2007).…”
Section: Pod In Health Carementioning
confidence: 99%
“…In provision, there is also a difference between right and left. Although Howard’s Conservative federal government had supported private sector utilization and has promoted the privatization of “problem” public hospitals (Cook, 2006), the ALP has opposed privatization of public hospitals (ALP, 2007).…”
Section: Pod In Health Carementioning
confidence: 99%
“…All had Australian citizenship and so were entitled to basic health care, including subsidized general medical care under Medicare and subsidized medication through the Pharmaceutical Benefits Scheme. 39,40 All had been diagnosed with type 2 diabetes at least 5 years earlier, were taking oral medication or using insulin, and had no directly associated complications of diabetes, such as nephropathy, retinopathy or microvascular disease. Six (two Greek, two Indian, one Chinese and one Samoan) participants reported that they had been diagnosed with depression and had been prescribed antidepressants; two respondents were taking anti-depressants at time of interview.…”
Section: Study Setting and Participantsmentioning
confidence: 99%